Collateral damage : women write about war - Mujica, Barbara Louise (University of Virginia Press, 2021)
"An anthology of writings by women on war. Tells the stories of those who struggle on the margins of armed conflict or who attempt to rebuild their lives after a war, giving voice to the experiences of the mothers, sisters, friends, children, and victims of those who fight, as well as to female combatants. Includes fiction, poetry, drama, reportage, and other forms of nonfiction"--